The genetic stability of date palm shoots regenerated from leaves explant - Arafa, Rasha N.; Elsayh, Sayed A.A.; Abdalgaleel, Marwa M.; El-Habashy, Salwa; Ahmed, Emadeldin A.H.; Afifi, Eman H.; Draz, Alaa N.; Aramany, Rabab W. El; Sharkh, Abdallah; El-Kader, Mohamed T. Abd; Barakat, Ahmed A.M.; Hoda A.A., Dosoky (International Journal of Environment, Agriculture and Biotechnology, 2023)
The purpose of this research was to develop a micro-propagation method for the date palm Zaghlol cv. using juvenile leaves. To produce the necessary results, different plant growth regulator combinations were used. The leaves were grown on MS medium supplemented with PVP to prevent the explants from browning. The results showed that adding PVP at a concentration of 1.0 g/l considerably reduced browning. On the induction medium, callus formation occurred during the fourth week of culture; however, callus formation (87.5%) was more prevalent on the ¾ MS medium containing with 10.0 mg/l NAA, 1.0 mg/l BA and 2.0 mg/l 2ip. The greatest development of embryogenic callus (94.50%) occurred on a ¾ MS medium supplemented with 5.0 mg/l NAA and 2.0 mg/l BA. The largest fresh callus weight (3.53 g) was produced by this treatment after four months in culture. On MS medium supplemented with 2.0 TDZ, 1.5 BA and 0.5 NAA, which was regarded as the optimum medium for increasing the number of embryos to 32.10 embryos/culture, the best results (65.67%) were obtained. Further investigation into the stimulation and development of somatic embryogenesis involved using MS basal medium supplemented with BA at 0.5 mg/l, kin at 0.1 mg/l and NAA at 0.05 mg/l; this treatment formed the most leaves (20.11 leaf/cluster). The cluster of shoots grown on MS basal medium supplemented with BA at 2.0 mg/l and NAA at 0.5 mg/l had the highest leaf number (34.25 leaf/cluster) and leaves length values after three sub-cultures (4.75 cm). The DNA-based fingerprinting technology ISSR was used to confirm the genetic stability of this protocol. The mother tree and tissue culture-derived shoots evaluated exhibited no differences in the ISSR banding patterns. The micro-propagation method could be used to produce genetically stable date palm plants.